Propuesta de desarrollo del sistema de transporte fluvial como potencial turístico – urbano de durán para transferencia de pasajeros. - Ruilova Mosquera, Cristina (2009)
River tourism is currently positioning itself as an economic activity of great interest, especially in areas with this water resource and that in turn creates great appreciation of landscape and environmental value, which can be described as sustainable because the impact on the environment is not significant. This proposal is the development of river transport system in the canton Duran like as tourism potential, offering an alternative that generates tourism visits to the district through this waterway promoting tourism development in the township and its attractions over the adequacy from one terminal to concentrate and map the flow of visitors it receives to the different points of interest causing the interaction between residents and tourists.